Microfinance and Mechanism Design: The Role of Joint Liability and Cross-Reporting - Zulkefly Abdul Karim (International Journal of Management Studies, 2010)
Since the establishment of Grameen Bank in 1976 by Professor MuhammadYunus1, many economists have studied extensively, either theoretically or empirically, the success of the Grameen Bank in eradicating the poverty problem in Bangladesh. Therefore, this paper aims to apply the mechanism design theory in microfinance by examining the role of joint liability and cross reporting mechanism in the loan contract which is designed by microfinance lender. In doing so, this study simplified the joint liability mechanism proposed by Ghatak (1999, 2000) and cross-reporting mechanism by Rai and Sjostrom (2004). Based on the joint-liability mechanism, it is clearly stated that the microfinance lender can minimise or avoid the adverse selection problem in the credit market through peer selection and peer screening. In the meantime, the joint liability mechanism is better than individual lending in terms of increasing the social welfare among the poor borrower, charging lower interest rates, and generating high repayment rates. In contrast, Rai and Sjostrom (2004) argued that joint liability alone is not enough to efficiently induce borrowers to help each other. Indeed, the cross-reporting mechanism is also important for lenders in order to minimise the problem of asymmetric information in the credit market. The cross-reporting mechanism is also efficient because it can influence the borrower to be truthful-telling about the state of the project and subsequently can minimise the deadweight loss (punishment) among the borrowers. In comparison, without cross reporting, the lending mechanism is inefficient because the borrower will be imposed harsh punishment from the bank and the bank can undertake auditing or verify the state of the project and punish accordingly.